A Comparative Lexical Study of Qur'ānic Arabic - Zammit, Martin, (Handbook of Oriental Studies. Section 1 The Near and Middle East ;, 2002)
This work does not aim to be an etymological dictionary of Qur'ānic Arabic, nor does it attempt to suggest some new genetic classification of the Semitic languages. Rather, it offers insights into the internal lexical relationships attested in a number of Semitic varieties. The work is based on a quantitative analysis of a substantial corpus of the Arabic lexicon with a view to investigating lexical relationships within a number of Semitic languages. Qur'ānic Arabic is the source of a lexical mass comparison exercise involving Akkadian, Ugaritic, Aramaic, Syriac, Hebrew, Phoenician, Epigraphic South Arabian and Ge'ez. Moreover, the lexical links identified in this study are in themselves linguistic indicators of the various degrees of cultural proximity characterising the various Semitic languages.